Autecological characteristics of Centaurea hermannii F. Herm an endemic species from Turkey - ÖZYİĞİT, İBRAHİM İLKER; YARCI, CELAL (My University, 2014)
© 2014, National Centre for Agrarian Sciences. All rights reserved.This study was performed on Centaurea hermannii F. Herm to acquire information about some characteristics (bioclimatic, edaphic, topographic, biotic etc.) of its habitat and distribution in Istanbul-Turkey. Plant and soil samples were collected between Subaşı and Akalan Villages, in Catalca District of Istanbul. Soil texture, structure and other physical and chemical measurements such as pH, electrical conductivity (EC), saturation, salinity, organic matter, CaCO3 content were determined by using various analyses. The result showed that the soils where plants grow on consist of 34% sand, 34% silt and 32% clay. In the plants, the average contents of some elements (%) were measured as 1.05, 1.05, 2.93 for N, 0.015, 0.02 and 0.034 for P, 0.026, 0.025 and 0.029 for Na, 1.46, 2.58 and 1.90 for K, 1.70, 0.48 and 1.70% for Ca in roots, stems and leaves, respectively. The values above were compared with the values of other Centaurea species in different regions of Turkey.
Keywords: Sağlık Bilimleri; Veteriner Bilimleri; Tarımsal Bilimler; Ziraat; Health Sciences; Veterinary Sciences; Agricultural Sciences; Agriculture; Tarım ve Çevre Bilimleri (AGE); Bitki ve Hayvan Bilimleri; Tarım Bilimleri; VETERİNERLİK BİLİMLERİ; ZİRAAT MÜHENDİSLİĞİ; Agriculture & Environment Sciences (AGE); PLANT & ANIMAL SCIENCE; AGRICULTURAL SCIENCES; VETERINARY SCIENCES; AGRICULTURAL ENGINEERING; Genel Veterinerlik; Genel Tarım ve Biyoloji Bilimleri; Yaşam Bilimleri; General Veterinary; General Agricultural and Biological Sciences; Life Sciences; Asteraceae; Mineral nutrition; Plant-soil interactions; Asteraceae; plant-soil interactions; mineral nutrition